Opportunities and challenges in integrating disabled employees in UiTM Pahang / Hasnizawati Hashim, Musramaini Mustapha and Norzie Diana Baharum - Hashim, Hasnizawati; Mustapha, Musramaini; Baharum, Norzie Diana (2015)
Integrating the disabled in an organization is not an easy task. It demands a lot of changes in order to suit the disabled's needs - without which, a successful integration in the workplace can be compromised. Within 30 years of its establishment, UiTM Pahang has taken a bold action in fulfilling the corporate social responsibility in hiring people with disabilities. Job opportunities are widely opened for the disabled as qualification is the main factor in determining their employability in the campus. A semi structured interview with the Rector of UiTM Pahang was used to get a clear view on its implementation. It is found that there is an indication of facing challenges in hiring the disabled but opportunities do exist while integrating them in the UiTM Pahang workplace.